Juan Luna his life, his art, and its relevance to art education - Zafaralla, Paulino Blanco 1938- (1973)
The study aims to provide a descriptive discussion on the life of Juan Luna and his art with a view of locating the content of his patriotism as expressed in his works, and to find out other aspects of his art and the relevance of his art to art education.
Thesis (M.A.)--University of the Philippines.
Keywords: Luna, Juan -- 1857-1899.; Art, Philippine; Painting, Philippine